2014
DOI: 10.4033/iee.2014.7.16.c
|View full text |Cite
|
Sign up to set email alerts
|

Estimating fitness from offspring counts in clonal seed plants

Abstract: Should asexual/vegetative offspring be counted in estimates of evolutionary fitness in seed plants? The answer it seems remains debatable among evolutionary ecologists. Arguably, however, the answer is yes when fitness is ascribed strictly to resident genes/alleles, in terms of their survival-through copying and transmission success-over time. This success results only because sporophyte 'rooted units' make more 'rooted units'-not primarily in terms of leaving descendent 'individuals', but more fundamentally a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…in the most severely crowded vegetation, where most resident plants (regardless of their potential body sizes) are forced to remain at only a fraction of their species potential. Moreover, within such vegetation, recent research (Tracey & Aarssen 2011, 2014 has shown that species with higher numerical abundance generally have a relatively small maximum potential body size (MAX) and that this is associated with a relatively small minimum reproductive threshold size (MIN). In terms of success under competition, therefore, smaller species may have a 'reproductive economy advantage', conferring higher numerical abundance and hence increased gene copying and transmission success to future generations (Aarssen 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…in the most severely crowded vegetation, where most resident plants (regardless of their potential body sizes) are forced to remain at only a fraction of their species potential. Moreover, within such vegetation, recent research (Tracey & Aarssen 2011, 2014 has shown that species with higher numerical abundance generally have a relatively small maximum potential body size (MAX) and that this is associated with a relatively small minimum reproductive threshold size (MIN). In terms of success under competition, therefore, smaller species may have a 'reproductive economy advantage', conferring higher numerical abundance and hence increased gene copying and transmission success to future generations (Aarssen 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These relationships are of central importance to understanding the role of life history strategies in shaping the structure and function of plant communities, and in identifying accurate predictions for applied goals associated with habitat restoration and conservation. To address the above questions, therefore, we collected data from a two-season field experiment in the same old-field community used in Tracey & Aarssen (2011, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we refer to this as a lower “body mass density” (BMD), that is, dry mass per unit space occupancy. This is illustrated in Figure , where a single adult offspring (an individual “rooted unit”; Aarssen, ) produced by a parent plant belonging to a species with a large maximum potential body size (MAX) (Figure a) is depicted as having the same above‐ground space occupancy as 10 individual adult offspring produced by a parent plant belonging to a species with a much smaller MAX (Figure b). Total mass per individual plant (indicated by the amount of green space) is of course greater for the larger plant in Figure a, but there are more canopy mass “gaps” here (represented by the amount of white space) within the perimeter of space occupancy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we predict that (1) Our results have important implications for the interpretation of "reproductive economy" in plants, that is, capacity to produce at least some offspring despite growth or body size limitation (e.g., due to crowding/competition, or because of limited time available for growth, flowering, pollination, or fruit/seed maturation), and hence the probability of reproducing before death (Aarssen, 2008(Aarssen, , 2015Aarssen et al, 2006). Previous studies indicate that reproductive economy is generally greater in smaller species because of a relatively small minimum reproductive threshold size (MIN) (Tracey & Aarssen, 2011, 2014Nishizawa & Aarssen 2014). The present results suggest that greater reproductive economy in smaller species may also be promoted by a relatively high fecundity per unit plant body space occupancy-because of a generally higher BMD in smaller species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation